Xylanase production by Penicillium sp. Pn004 and its application for grass hydrolysis: High value subproduct from non-centrifugal sugarcane bagasse and wheat bran - Martínez, Anny Daniela (2024)
Worldwide more than 7 billion tons of lignocellulosic biomass will be produced by 2025. In Colombia, these residues are mainly disposed of in rivers and open fields, and only 10% is reused and recycled. Non-centrifugal sugarcane bagasse (SCB) is a residue obtained after sugarcane juice extraction during the manufacturing process of panela and is mostly used as fuel for boilers at sugar mills. Wheat bran (WB) is the main waste from wheat flour production. Nonetheless, the chemical composition of these by-products makes them suitable for use as substrates for hemicellulolytic enzyme production from fungi. Here, a whole process for production in a solid-state fermentation system, recovery, and ultrafiltration process for concentration of xylanases by Penicillium sp. Pn004 is presented. The higher productivity (26.7 ± 1.59 U gds-1 day-1) was reached on the fifth day of fermentation with an enzyme activity of 130.0 ± 7.95 U gds-1. The batch ultrafiltration process allowed increasing the xylanase activity up to 19-fold in the retentate, from 66.47 U mL-1 to 1486.83 U mL-1, without reaching a steady state flux through the membrane. Finally, the enzymatic extract achieved a 43% release of sugar from kikuyu grass (Cenchrus clandestinus), showing its potential to be used as an additive for silage or for enzymatic saccharification of lignocellulosic materials for sugar production.